Quantitative Evaluation of the Association Between Fixation Stability and Phoria During Short-Term Binocular Viewing - Kim, Sang-Yeob; Moon, Byeong-Yeon; Cho, Hyun Gug; Yu, Dong-Sik (Frontiers in Neuroscience, 2022)
Purpose: Fixation stability for binocular anomalies with a phoria cannot be detected by direct observations. This study aimed to quantitatively evaluate fixation stability using an eye tracker rather than direct directions in binocular vision with abnormal and normal phorias. Methods: Thirty-five and 25 participants with abnormal and normal phoria, respectively, were included in the study. The horizontal and vertical gaze points and convergence were recorded for 10 s using a remote eye tracker while binocularly viewing a target on a display screen 550 mm away. Fixation stability was quantified using bivariate contour ellipse areas (BCEA). Results: The fixation stability for all participants-based evaluations as a single cluster in the abnormal phoria group was lower than that in the normal phoria group (p = 0.005). There was no difference between the two groups in the evaluation based on the BCEA for each participant-based evaluation (p = 0.66). Fixation stability was also more related to convergence for the abnormal phoria group than for the normal phoria group (r = 0.769, p < 0.001; r = 0.417, p = 0.038, respectively). Conclusions: As the first study to evaluate fixation stability using an eye-tracker to differentiate between abnormal and normal phoria for non-strabismus, these findings may provide evidence for improving the evaluation of binocular vision not detected with clinical diagnostic tests.